Production process for improving lubricating property of fiber oil agent

By using nanolubricants of nano calcium carbonate and composite nanoboronitride in fiber oil agents, the problem of unstable lubricating performance of fiber oil agents is solved, significantly improving the lubricating performance and stability of fiber oil agents and extending the service life of production equipment.

CN119800558APending Publication Date: 2025-04-11TAICANG YUESHUN OIL PROD GREASE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411994339.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The lubricating properties of existing fiber oil agents are unstable, which affects the smoothness of the spinning process and the quality of the final product.

Method used

Using a production process, by mixing fatty alcohol polyoxyethylene ether, alkyl ether sulfate, oleyl alcohol esters, thickeners, nanolubricants, antioxidants with preservatives, stirring with high-speed disperser, and then filtering to remove larger particles to obtain a fiber oil agent. In this process, nano calcium carbonate and composite nanoboronitride are used as nanolubricants to reduce the fiber friction contact rate by depositing the film.

Benefits of technology

It greatly improves the lubricating performance of fiber oil agents, reduces the number of fibers breaks during spinning, extends the service life of production equipment, and improves the stability and mechanical strength of fiber oil agents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a production process of a fiber oiling agent for improving lubricating property, which comprises the following steps: pretreatment: mixing fatty alcohol-polyoxyethylene ether, alkyl ether sulfate, oleic acid oleyl ester, a thickening agent, a nano lubricant, an antioxidant and a preservative, and uniformly stirring to obtain a mixture; mixing and stirring: stirring and dispersing by using a high-speed dispersion machine so that the mixture is uniformly stirred and fully mixed; filtering: filtering the fully mixed substances to remove larger particles so that the system is uniform, thereby obtaining the fiber oiling agent; the nano thickening agent comprises nano calcium carbonate and composite nano boron nitride. The fiber oiling agent has the effect of improving the lubricating performance of the fiber oiling agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fiber oils, and in particular to a production process for improving the lubricating properties of fiber oils. Background Art

[0002] Currently, in the textile industry, fiber oil is usually added during the spinning process to reduce friction between fibers. However, existing fiber oils often have unstable lubrication properties, which not only affects the smoothness of the spinning process, but also leads to fluctuations in the quality of the final product. With the growing market demand for high-quality textiles, the development of a method that can effectively improve the lubrication properties of fiber oils has become an urgent need in the industry.

[0003] In order to improve the lubrication performance of fiber oil, the methods commonly adopted in the industry include adjusting the type and proportion of base oil, introducing specific additives or changing the production process conditions. For example, the overall lubricity of the oil can be enhanced by increasing the proportion of base oil with excellent anti-wear performance; or modifying components such as surfactants and extreme pressure agents can be added to reduce the friction at the fiber interface; and the finished product characteristics can be optimized by precisely controlling factors such as reaction temperature and pressure. However, these methods are either costly or difficult to apply on a large scale in industry. Summary of the invention

[0004] In order to further improve the lubricating properties of fiber oil, the present application provides a production process for improving the lubricating properties of fiber oil.

[0005] The present application provides a production process for improving the lubrication performance of fiber oils using the following technical solutions: A production process for improving the lubricating performance of a fiber oil comprises the following steps: Pretreatment: mixing fatty alcohol polyoxyethylene ether, alkyl ether sulfate, oleyl oleate, thickener, nano-lubricant, antioxidant and preservative, and stirring to obtain a mixture; Mixing and stirring: Use a high-speed disperser to stir and disperse the mixture so that it is evenly mixed and fully mixed; Filtration: Filter the fully mixed material to remove larger particles, make the system uniform, and obtain the fiber oil agent; the nano thickener includes nano calcium carbonate and composite nano boron nitride.

[0006] By adopting the above technical scheme, after adding nano-lubricants to the system, the lubrication performance of the fiber oil can be greatly improved, the number of breakages in the spinning process is reduced, and the service life of the production equipment is extended; after the nano-calcium carbonate contacts the fiber, it can be deposited on the fiber surface to form a deposition film, thereby reducing the friction contact rate and playing a role in reducing friction; the composite nano-boron nitride has good mechanical properties and can synergistically improve the friction resistance of the system when combined with nano-calcium carbonate, thereby further improving the nano-lubricant's improvement on the lubrication performance of the fiber oil.

[0007] Preferably, the modified nano boron nitride comprises boron nitride and manganese dioxide.

[0008] By adopting the above technical solution, the lubrication modification effect of a single nanoparticle on the fiber oil system is relatively simple. After the nano boron nitride is compounded with manganese dioxide, the overall lubrication performance of the system can be further improved.

[0009] Preferably, the composite nano boron nitride is prepared by the following method: Nano boron nitride is mixed with potassium permanganate, then added into water and stirred to obtain a composite dispersion, hydrochloric acid is added during the stirring process, after stirring, the temperature is increased and kept for a period of time, then cooled and centrifuged, washed and dried to obtain composite nano boron nitride.

[0010] By adopting the above technical scheme, boron nitride is ultrasonically peeled off to obtain nano boron nitride with fewer layers, and then a hydrothermal synthesis method is used to attach nano particles on the surface of boron nitride nano sheets by utilizing the chemical reaction of substances in an aqueous solution under high temperature and high pressure conditions, thereby making the nano boron nitride composite with manganese dioxide. The prepared composite nano boron nitride has the properties of small size, good dispersibility, uniformity and reduced agglomeration, thereby improving the lubrication performance, stability and mechanical strength of the fiber oil.

[0011] Preferably, the mass ratio between the composite nano-boron nitride and the nano-calcium carbonate is 1:(4.5-5.5).

[0012] By adopting the above technical solution, preferably the mass ratio between the composite nano-boron nitride and the nano-calcium carbonate is within the above range, which can further improve the stability of the prepared nano-lubricant.

[0013] Preferably, the mass of the nano-lubricant accounts for 6-8% of the total mass of the fiber oil.

[0014] By adopting the above technical solution, the mass of the nano-lubricant is preferably within the above range, which can further improve the overall stability of the prepared nano-lubricant.

[0015] Preferably, the thickener raw materials include poly-α-olefin 40, octadecylamine, cyclohexylamine and 4,4-diphenylmethane diisocyanate.

[0016] By adopting the above technical solution, poly-α-olefin is a non-polar polymer with good low-temperature and viscosity-temperature properties. Poly-α-olefin 40 is used to prepare a thickener to increase the viscosity of the fiber oil, so that the fiber oil can better contact the surface of the fiber, further improve the stability of the fiber oil, and at the same time improve the lubrication performance of the fiber oil.

[0017] Preferably, the thickener is prepared by the following method: Poly-α-olefin 40, octadecylamine and cyclohexylamine are heated to obtain organic oil, and then 4,4-diphenylmethane diisocyanate is mixed with poly-α-olefin 40, and the mixture is added into the organic oil after heating, and a thickener is obtained after stirring and cooling.

[0018] Preferably, the thickener accounts for 10-12% of the total mass of the fiber oil.

[0019] By adopting the above technical solution, the mass of the thickener is preferably within the above range, which can further improve the stability and lubrication performance of the prepared fiber oil.

[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. After adding nano-lubricant to the lubricating oil system, the lubrication performance of the fiber oil can be greatly improved, thereby reducing the number of fiber breakages during the spinning process and extending the service life of the production equipment. The nano-lubricant is deposited on the fiber surface to form a deposition film after the nano-calcium carbonate contacts the fiber surface, thereby reducing the friction contact rate of the fiber and playing a role in reducing friction. The layers of the nano-boron nitride layered structure material are bound by weak van der Waals forces and the layers are bound by ionic covalent bonds. Together with nano-calcium carbonate, it can improve the lubrication performance of the fiber oil, thereby improving the anti-wear performance of the fiber; 2. Ultrasonic exfoliation of nano-boron nitride is used to obtain nano-boron nitride with fewer layers, and then a hydrothermal synthesis method is used to attach manganese dioxide to the surface of the nano-boron nitride under high temperature and high pressure conditions. After the nano-boron nitride and manganese dioxide are composited, the composite nano-boron nitride has small size, good dispersibility, can be evenly dispersed in the system and reduce agglomeration, so as to further improve the lubrication and mechanical properties of the fiber oil; 3. A poly-α-olefin-based thickener is also added to the system to improve the viscosity of the system, thereby improving the bonding performance between the fiber oil and the fiber, and further enhancing the lubrication performance of the fiber oil. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples are commercially available; wherein the antioxidant is antioxidant 245 (CAS No.: 36443-68-2); and the preservative is kason (CAS No.: 26172-55-4).

[0022] Example 1 Preparation of composite nano boron nitride 10g of nano boron nitride (CAS No.: 10043-11-5) powder, 600g of isopropanol (CAS No.: 67-63-0) and 300g of deionized water were mixed, stirred evenly, ultrasonically dispersed for 2h, then centrifuged at a speed of 3000r / min for 3min, the supernatant was taken and continued to be centrifuged at a speed of 8000r / min for 5min, then washed with deionized water, and vacuum dried to obtain pre-treated nano boron nitride; 5g of pre-treated nano boron nitride was mixed with 10g of potassium permanganate, then added to 500g of deionized water and stirred for 10min to obtain a composite dispersion, 7.5g of hydrochloric acid was added during the stirring process, and after stirring, it was transferred to a reactor, kept warm at a temperature of 85°C for 20min, then cooled to 25°C, centrifuged at a speed of 5000r / min, repeatedly washed with deionized water for 3 times, and vacuum dried at a temperature of 40°C to obtain composite nano boron nitride.

[0023] Preparation of nanolubricants: The composite nano boron nitride and nano calcium carbonate are mixed at a mass ratio of 1:4.5 to obtain a nano lubricant.

[0024] Prepare the thickener: Add 15 g of poly-α-olefin 40 (CAS No.: 68037-01-4), 1.5 g of octadecylamine (CAS No.: 124-30-1), and 0.15 g of cyclohexylamine (CAS No.: 108-91-8) into a reaction kettle, heat to 70°C to obtain organic oil, then mix 2 g of 4,4-diphenylmethane diisocyanate (CAS No.: 101-68-8) with 1.35 g of poly-α-olefin 40, heat to 60°C, add to the organic oil, stir for 15 minutes, and cool to obtain a thickener.

[0025] Preparation of fiber oil with improved lubrication performance: Pretreatment: 33 g of fatty alcohol polyoxyethylene ether (CAS No.: 9002-92-0), 26 g of alkyl ether sulfate (CAS No.: 68611-29-0), 23 g of oleyl oleate (CAS No.: 17673-59-5), 10 g of thickener, 6 g of nanolubricant, 1 g of antioxidant and 1 g of preservative were mixed and stirred to obtain a mixture; Mixing and stirring: Use a high-speed disperser to stir at a speed of 5000r / min for 5 minutes to make the mixture evenly stirred and fully mixed; Filtration: Filter the fully mixed material to remove larger particles, make the system uniform, and obtain the fiber oil agent.

[0026] Example 2 Preparation of composite nano boron nitride 10 g of nano boron nitride powder, 600 g of isopropanol and 300 g of deionized water were mixed, stirred evenly, ultrasonically dispersed for 2 h, then centrifuged at 3000 r / min for 3 min, the supernatant was taken and continued to be centrifuged at 8000 r / min for 5 min, then washed with deionized water, and vacuum dried to obtain pre-treated nano boron nitride; 5 g of pre-treated nano boron nitride was mixed with 10 g of potassium permanganate, then added to 500 g of deionized water and stirred for 10 min to obtain a composite dispersion, 7.5 g of hydrochloric acid was added during the stirring process, and after stirring, it was transferred to a reactor, kept warm at 85° C. for 20 min, then cooled to 25° C., centrifuged at 5000 r / min, repeatedly washed with deionized water 3 times, and vacuum dried at a temperature of 40° C. to obtain composite nano boron nitride.

[0027] Preparation of nanolubricants: The composite nano boron nitride and nano calcium carbonate are mixed at a mass ratio of 1:5.5 to obtain a nano lubricant.

[0028] Prepare the thickener: 15 g of poly-α-olefin 40, 1.5 g of octadecylamine and 0.15 g of cyclohexylamine were added to a reaction kettle, and the temperature was raised to 70° C. to obtain an organic oil. Then, 2 g of 4,4-diphenylmethane diisocyanate was mixed with 0.35 g of poly-α-olefin 40, the temperature was raised to 60° C., and then added to the organic oil, stirred for 15 minutes, and cooled to obtain a thickener.

[0029] Preparation of fiber oil with improved lubrication performance: Pretreatment: 28 g of fatty alcohol polyoxyethylene ether, 24 g of alkyl ether sulfate, 22 g of oleyl oleate, 12 g of thickener, 8 g of nano lubricant, 3 g of antioxidant and 3 g of preservative were mixed and stirred to obtain a mixture; Mixing and stirring: Use a high-speed disperser to stir at a speed of 5000r / min for 5 minutes to make the mixture evenly stirred and fully mixed; Filtration: Filter the fully mixed material to remove larger particles, make the system uniform, and obtain the fiber oil agent.

[0030] Example 3 Preparation of composite nano boron nitride 10 g of nano boron nitride powder, 600 g of isopropanol and 300 g of deionized water were mixed, stirred evenly, ultrasonically dispersed for 2 h, then centrifuged at 3000 r / min for 3 min, the supernatant was taken and continued to be centrifuged at 8000 r / min for 5 min, then washed with deionized water, and vacuum dried to obtain pre-treated nano boron nitride; 5 g of pre-treated nano boron nitride was mixed with 10 g of potassium permanganate, then added to 500 g of deionized water and stirred for 10 min to obtain a composite dispersion, 7.5 g of hydrochloric acid was added during the stirring process, and after stirring, it was transferred to a reactor, kept warm at 85° C. for 20 min, then cooled to 25° C., centrifuged at 5000 r / min, repeatedly washed with deionized water 3 times, and vacuum dried at a temperature of 40° C. to obtain composite nano boron nitride.

[0031] Preparation of nanolubricants: The composite nano-boron nitride and nano-calcium carbonate are mixed in a mass ratio of 1:5 to obtain a nano-lubricant.

[0032] Prepare the thickener: 15 g of poly-α-olefin 40, 1.5 g of octadecylamine and 0.15 g of cyclohexylamine were added to a reaction kettle, and the temperature was raised to 70° C. to obtain an organic oil. Then, 2 g of 4,4-diphenylmethane diisocyanate was mixed with 0.85 g of poly-α-olefin 40, the temperature was raised to 60° C., and then added to the organic oil, stirred for 15 minutes, and cooled to obtain a thickener.

[0033] Preparation of fiber oil with improved lubrication performance: Pretreatment: 28 g of fatty alcohol polyoxyethylene ether, 25 g of alkyl ether sulfate, 21 g of oleyl oleate, 11 g of thickener, 7 g of nano lubricant, 4 g of antioxidant and 4 g of preservative were mixed and stirred to obtain a mixture; Mixing and stirring: Use a high-speed disperser to stir at a speed of 5000r / min for 5 minutes to make the mixture evenly stirred and fully mixed; Filtration: Filter the fully mixed material to remove larger particles, make the system uniform, and obtain the fiber oil agent.

[0034] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the nano-lubricant, 3.75 g of composite nano-boron nitride and 18.75 g of nano-calcium carbonate are used.

[0035] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the nano-lubricant, 1.875 g of composite nano-boron nitride and 16.875 g of nano-calcium carbonate are used.

[0036] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, 1.5 g of 4,4-diphenylmethane diisocyanate is used in preparing the thickener.

[0037] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 3.5 g of 4,4-diphenylmethane diisocyanate is used when preparing the thickener.

[0038] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 4 g of nano-lubricant and 31 g of fatty alcohol polyoxyethylene ether are used in preparing the fiber oil.

[0039] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the fiber oil agent, 10 g of nano lubricant and 25 g of fatty alcohol polyoxyethylene ether are used.

[0040] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the fiber oil agent, 8 g of thickener and 31 g of fatty alcohol polyoxyethylene ether are used.

[0041] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the fiber oil agent, 14 g of thickener and 25 g of fatty alcohol polyoxyethylene ether are used.

[0042] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the nano-lubricant, the composite nano-boron nitride is prepared by physically mixing nano-boron nitride and nano-manganese dioxide in a ratio of 1:5.

[0043] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that in Example 13, when preparing the nano-lubricant, the composite nano-boron nitride is replaced with ordinary boron nitride.

[0044] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the nano calcium carbonate in the nano lubricant is replaced by an equal amount of composite nano boron nitride.

[0045] Comparative Example 2 Comparative Example 2 is based on Example 3, and the thickener in Comparative Example 2 is only poly-α-olefin.

[0046] Performance testing The following performance tests were performed on the samples of Examples 1-13 and Comparative Examples 1-2: (1) Anti-friction performance The fiber oil agent was coated on the surface of the polyester fiber and allowed to stand for 48 hours. The friction coefficient of the polyester fiber coated with the fiber oil agent was tested. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.

[0047] Table 1 Performance test results of Examples 1-13 and Comparative Examples 1-2 Test items Friction coefficient Example 1 0.108 Example 2 0.110 Example 3 0.102 Example 4 0.132 Example 5 0.130 Example 6 0.124 Example 7 0.136 Example 8 0.142 Example 9 0.155 Example 10 0.120 Embodiment 11 0.144 Example 12 0.192 Embodiment 13 0.228 Comparative Example 1 0.292 Comparative Example 2 0.177 As shown in Table 1, the friction resistance of Examples 1-3 is 0.110 or less, which indicates that the fiber oil prepared in the present application has the effect of improving the lubrication performance of the fiber.

[0048] In Example 4 and Example 5, when preparing the nano-lubricant, the mass ratio between the composite nano-boron nitride and the nano-calcium carbonate is not within the range specified in the present application. When the content of nano-boron nitride is too much, the content of nano-calcium carbonate is too little, and it is difficult to deposit a sufficient amount of nano-calcium carbonate particles on the fiber surface and to fill the micro-defect area. Therefore, the sample of Example 4 is difficult to further improve the wear resistance of the fiber; when the content of nano-boron nitride is too little, the content of nano-calcium carbonate is too much, which will increase the deposition amount on the fiber friction surface and affect the lubrication performance of the system. At the same time, too much nano-calcium carbonate will agglomerate in the system, further affecting the stability of the fiber oil agent. Therefore, the performance of Example 4 and Example 5 are both reduced.

[0049] In Examples 6 and 7, when preparing the thickener, the content of 4,4-diphenylmethane diisocyanate used is not within the range specified in the present application. When the content of 4,4-diphenylmethane diisocyanate is too little, it is difficult to further increase the viscosity of the thickener system, making it difficult to further improve the adhesion performance of the prepared fiber oil agent, and also affecting the lubrication performance of the system; when the content of 4,4-diphenylmethane diisocyanate is too much, the viscosity of the thickener is too high, thereby affecting the uniformity and stability of the fiber oil agent, so the performance of Examples 6 and 7 are both reduced.

[0050] When preparing the fiber oil agent in Example 8 and Example 9, the proportion of the nanolubricant in the system is not within the range specified in the present application. When the content of the added nanolubricant is too little, it is difficult for the too little nanolubricant to fully fill the fiber surface repair grooves, and it is difficult to further improve the overall mechanical properties of the fiber, thereby affecting the overall lubrication performance and mechanical strength of the fiber; when the content of the nanolubricant is too much, too many nanofillers will agglomerate in the system, thereby affecting the overall stability of the system, so the performance of Example 8 and Example 9 are both reduced.

[0051] When preparing the fiber oil agent in Example 10 and Example 11, the proportion of the thickener in the system is not within the range specified in the present application. When the thickener content is too little, the viscosity of the system is too low, and it is difficult to stably adhere to the fiber surface, thereby reducing the bonding performance between the fiber oil agent and the fiber, reducing the stability, and affecting the comprehensive performance of the system; when the thickener content is too much, the viscosity of the system is too high, it will make it difficult for the components of the fiber oil agent to be evenly dispersed in the system, thereby affecting the comprehensive performance of the fiber oil, so the performance of Example 10 and Example 11 are both reduced.

[0052] In Example 12, when preparing the nano-lubricant, the composite nano-boron nitride is prepared by physically mixing nano-boron nitride and nano-manganese dioxide. It is difficult to improve the dispersibility and bonding performance of the composite nano-boron nitride obtained by ordinary physical mixing. The composite nano-boron nitride agglomerates in the system, affecting the stability of the system. Therefore, the performance of Example 12 is reduced.

[0053] In Example 13, the composite nano-boron nitride is replaced with ordinary boron nitride. The dispersibility of ordinary boron nitride in the system is difficult to improve, and agglomeration occurs in the system, affecting the overall stability of the system. Therefore, the performance of Example 13 is reduced.

[0054] In Comparative Example 1, the nano-lubricant is only nano-boron nitride, and the nano-lubricant without the addition of nano-calcium carbonate is difficult to form a deposition film on the fiber surface, and it is difficult to synergistically improve the lubrication performance of the fiber. Therefore, the lubrication performance of Comparative Example 1 decreases.

[0055] In Comparative Example 2, the thickener is only poly-α-olefin, and the stability of the unimproved poly-α-olefin in the system is difficult to improve, so the stability of the prepared fiber oil is difficult to further improve, so the performance of Comparative Example 2 is reduced.

[0056] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A production process for improving the lubricating properties of fiber oil, characterized in that: The steps include: Pretreatment: mixing fatty alcohol polyoxyethylene ether, alkyl ether sulfate, oleyl oleate, thickener, nano-lubricant, antioxidant and preservative, and stirring to obtain a mixture; Mixing and stirring: Use a high-speed disperser to stir and disperse the mixture so that it is evenly mixed and fully mixed; Filtration: Filter the fully mixed material to remove large particles, make the system uniform, and obtain the fiber oil; The nano thickener comprises nano calcium carbonate and composite nano boron nitride.

2. A production process for improving the lubricating performance of fiber oil according to claim 1, characterized in that: The composite nano boron nitride comprises boron nitride and manganese dioxide.

3. A production process for improving the lubricating performance of fiber oil according to claim 2, characterized in that: The composite nano boron nitride is prepared by the following method: Nano boron nitride is mixed with potassium permanganate, then added into water and stirred to obtain a composite dispersion, hydrochloric acid is added during the stirring process, after stirring, the temperature is increased and kept for a period of time, then cooled and centrifuged, washed and dried to obtain composite nano boron nitride.

4. A production process for improving the lubricating performance of fiber oil according to claim 1, characterized in that: The mass ratio between the composite nano-boron nitride and the nano-calcium carbonate is 1:(4.5-5.5).

5. A production process for improving the lubricating performance of fiber oil according to claim 1, characterized in that: The mass of the nano-lubricant accounts for 6-8% of the overall mass of the fiber oil.

6. A production process for improving the lubricating performance of fiber oil according to claim 1, characterized in that: The thickener raw materials include poly-alpha-olefin 40, octadecylamine, cyclohexylamine and 4,4-diphenylmethane diisocyanate.

7. A production process for improving the lubricating performance of fiber oil according to claim 6, characterized in that: The thickener is prepared by the following method: Poly-α-olefin 40, octadecylamine and cyclohexylamine are heated to obtain organic oil, and then 4,4-diphenylmethane diisocyanate is mixed with poly-α-olefin 40, and the mixture is added into the organic oil after heating, and a thickener is obtained after stirring and cooling.

8. The production process for improving the lubricating performance of fiber oil according to claim 1, characterized in that: The thickener accounts for 10-12% of the overall mass of the fiber oil.